2011
DOI: 10.1371/journal.pone.0017461
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Mechanisms of Temporal Processing Deficits in Parkinson's Disease

Abstract: BackgroundParkinson's disease (PD) disrupts temporal processing, but the neuronal sources of deficits and their response to dopamine (DA) therapy are not understood. Though the striatum and DA transmission are thought to be essential for timekeeping, potential working memory (WM) and executive problems could also disrupt timing.Methodology/FindingsThe present study addressed these issues by testing controls and PD volunteers ‘on’ and ‘off’ DA therapy as they underwent fMRI while performing a time-perception ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
2
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 59 publications
(80 reference statements)
5
91
2
10
Order By: Relevance
“…One such disease, Parkinson disease, involves cognitive dysfunction (37) that can manifest as a dysexecutive syndrome (38) with impaired temporal control (9). Although temporal processing and executive function in Parkinson disease can be heterogeneous (37,39), impairment in these processes in Parkinson disease is likely related to dysfunctional mesocortical networks (12,18,40). The present study provides data demonstrating that prefrontal dopamine is crucial to timing, and that stimulation of D1 systems in prefrontal cortex can facilitate temporal control.…”
Section: Discussionmentioning
confidence: 68%
“…One such disease, Parkinson disease, involves cognitive dysfunction (37) that can manifest as a dysexecutive syndrome (38) with impaired temporal control (9). Although temporal processing and executive function in Parkinson disease can be heterogeneous (37,39), impairment in these processes in Parkinson disease is likely related to dysfunctional mesocortical networks (12,18,40). The present study provides data demonstrating that prefrontal dopamine is crucial to timing, and that stimulation of D1 systems in prefrontal cortex can facilitate temporal control.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, we can only assume that PD patients have deficit in planning the temporal features of sequential finger movements when the interval between two successive movements is supra-second, but we cannot discern whether this represents a distorted mental representation of time or, rather, defective spatio-temporal integration during motor planning. The data present in the literature so far support both interpretations, showing that PD patients are impaired in pure time processing tasks [56,57], but also in sensorimotor integration processes [58,59]. However an ad hoc study designed to correlate perceptual timing with motor planning ability in patients with PD might be useful to shed more light on the function of basal ganglia and interconnected cortical areas on this issue.…”
Section: Discussionmentioning
confidence: 84%
“…Though several studies have reported improvements in cognition in PD patients while on dopamine replacement therapy (e.g. levodopa) when compared to off treatment [37,38], these results are not consistent [39], supporting the notion that PD is a complex disease. In the literature reported here, only one study provided information on non-motor symptoms: two patients had intellectual impairment and only one subject presented with hallucinations [22].…”
Section: Discussionmentioning
confidence: 99%